Consumer perceived ethicality of banks in the era of digitalisation: The case of Poland - Piotrowski, Dariusz (Economics and Business Review, 2022)
Ethically conducted business has a positive impact on consumer trust, satisfaction and loyalty. The aim of this paper is to identify the bank activities that customers perceive as ethical and to what extent they affect consumer perceived ethicality. The binomial logit model applied in this study demonstrates that the honesty of financial advice, use of e-banking services and use of artificial intelligence technology to improve the quality of banking services have a significantly positive impact on consumers’ perception of banks in Poland as ethical institutions. Significant variables that negatively influence consumer perceived ethicality include gender, education, use of financial advisory services, banks’ manipulation of information about financial products and use of personal data against the will of customers.